Developing RME-based Mathematics Textbook to Improve Students’ Numeracy Skills and Learning Motivation - Siregar, Latifah; Asmin, Asmin; Arnita, Arnita (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
Referring to PISA 2015 and 2018 data, Indonesian students' mathematics skills, especially numeracy skills, are lower than the global average score. One effort that can be made to improve students' numeracy skills and learning motivation is the development of mathematics textbook based on Realistic Mathematics Education (RME) with relevant contexts that students can imagine. So, this study aims to develop RME-based mathematics textbook to improve students' numeracy skills and learning motivation using the context of Nai Marbittang, one of the popular folklores in South Tapanuli, North Sumatra, Indonesia. The researchers used the ADDIE development model to develop textbook while assessing its validity through expert validation sheets, practicality through questionnaires, and effectiveness through motivation questionnaires and numeracy tests. Through this study, the products developed were proven to be valid, practical, and effective in improving students' numeracy skills and learning motivation so it can be used more widely, especially on the Pythagorean theorem topic. Other researchers can also utilize folklores on various mathematics topics to improve students' numeracy and learning motivation.